Development and Characterization of Essential Oil Emulsion Formulation as a Natural Antibacterial Agent in Wound Healing Application - Chaudhary, Anupama; Kumar, Sachin (Journal of Neonatal Surgery, 2025)
The current study focuses on the development and comprehensive evaluation of a novel emulgel formulation containing Mirabilis jalapa root extract and clove oil, aimed at enhancing wound healing efficacy through a synergistic herbal approach. Emulgels, due to their dual advantage of emulsion-based drug solubilization and gel-based controlled release, serve as an ideal carrier for topical delivery of plant-derived bioactives. The formulation process involved systematic variation of gelling agents, emulsifiers, and oil-to-water ratios, resulting in an optimized formulation with suitable pH (6.1), viscosity, spreadability, and homogeneity. Stability assessments and HPTLC profiling confirmed the formulation’s chemical integrity over a 3-month period. LC-MS analysis identified twelve key phytochemicals, including eugenol, eugenyl acetate, apigenin, kaempferol, rutin, luteolin, ferulic acid, and quercetin, known for their antimicrobial, anti-inflammatory, antioxidant, and regenerative properties. To understand the underlying molecular mechanisms, a network pharmacology study was conducted, revealing significant interactions between these compounds and genes involved in wound healing, such as IL6, TNF, MMP9, TP53, and EGFR. The constructed network contained 44 nodes and over 100 edges, highlighting the multitarget capabilities of the formulation. Gene ontology enrichment further confirmed associations with biological processes like burn wound healing, oxidative stress response, inflammation, and skin development. This multidisciplinary study underscores the significance and novelty of combining traditional herbal knowledge with modern delivery systems and systems biology tools. The findings suggest that the Mirabilis jalapa–clove oil emulgel holds great promise as a natural, safe, and effective topical agent for managing wounds. Future work will focus on in vivo validation, clinical evaluation, and expanding its applications to chronic and infected wound conditions.